Karakteristik Penderita Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di Rsud Andi Makkasau Kota Parepare - Imelda Imelda; Henni Kumaladewi Hengky; Herlina Muin (Jurnal Kesehatan Nusantara (JKN), 2025)
Chronic renal failure (Chronic Kidney Disease) is a spectrum of different pathophysiological processes associated with impaired renal function and a progressive decrease in the Glomerular Filtration Rate (GFR). The term chronic renal failure (CKD) applies to the process of significant continuous and irreversible reduction in the number of nephrons and usually in stages 3-5. In this study, there were six characteristics of CKD patients undergoing hemodialysis at Andi Makkasau Hospital, Parepare City in terms of age, history of diabetes mellitus, hypertension, blood urea levels, blood creatinine levels, and hemoglobin levels.The results showed that the characteristics of patients with chronic kidney failure undergoing hemodialysis at the Andi Makkasau Hospital, Parepare City who experienced a high risk in terms of age were 67.2%, hypertension 55.6%, history of diabetes mellitus 47.8%, blood urea 77 ,6%, blood creatinine levels 74,6% and hemoglobin levels 68,7. It is recommended for patients with chronic kidney failure to monitor their health conditions and by reducing their intake of high-protein foods such as milk, eggs, and nuts, so that serum urea and creatinine levels can be controlled